Can perceivers recognise emotions from spontaneous expressions?. Issue 3 (3rd April 2018) - Sauter, Disa A.; Fischer, Agneta H.
ABSTRACT: Posed stimuli dominate the study of nonverbal communication of emotion, but concerns have been raised that the use of posed stimuli may inflate recognition accuracy relative to spontaneous expressions. Here, we compare recognition of emotions from spontaneous expressions with that of matched posed stimuli. Participants made forced-choice judgments about the expressed emotion and whether the expression was spontaneous, and rated expressions on intensity (Experiments 1 and 2) and prototypicality (Experiment 2). Listeners were able to accurately infer emotions from both posed and spontaneous expressions, from auditory, visual, and audiovisual cues. Furthermore, perceived intensity and prototypicality were found to play a role in the accurate recognition of emotion, particularly from spontaneous expressions. Our findings demonstrate that perceivers can reliably recognise emotions from spontaneous expressions, and that depending on the comparison set, recognition levels can even be equivalent to that of posed stimulus sets.